HF Radar observations of the Dardanelles outflow current in North Eastern Aegean using validated WERA HF radar data - KOKKINI, Z.; POTIRIS, M.; KALAMPOKIS, A.; ZERVAKIS, V. (Mediterranean Marine Science, 2014)
A two-site WERA HF radar station was installed in November 2009 at the eastern coast of Lemnos Island in North Aegean Sea, aiming to monitor the surface inflow of Black Sea waters exiting from the Dardanelles Strait, as well as to constitute a coastal management tool for incidents of oil-pollution or save-and-rescue operations. Strong interference by foreign transmissions is a source of noise deteriorating the quality of the backscattered signal, thus significantly reducing the HF radar’s effective data return rate. In order to ameliorate this problem, further quality-control and data gap interpolating procedures have been developed and applied, to be used in addition to the procedures incorporated and used by the manufacturer’s signal processing software. The second-level processing involves traditional despiking in the temporal domain, preceding Empirical Orthogonal Function analysis. The latter is used not only to filter high-frequency noise but also to fill data gaps in time and space. The data reconstruction procedure has been assessed via comparison of (a) HF radial with CODE-type drifter radial velocities as well as (b) HF-derived virtual drifter tracks with actual drifter tracks. The main circulation features and their variability, as revealed by the reconstructed fields, are presented.